Inequality, disadvantage and the capability approach: Bridging conceptual framework and empirical analysis - Rod Hick (Social Work and Society)
In this paper, I will discuss some of the challenges that arise when seeking to apply the capability to empirically examine poverty, inequality and welfare state change. I will begin by outlining the key concepts of the approach and its claims of distinctiveness vis-à-vis alternative approaches. Debates about how to apply the approach empirically have loomed large in the capability literature and I will discuss the challenges which emerge when trying to apply the approach in order to analyse poverty, and will point to some of the key conclusions that emerge from such studies. I will then argue that trying to apply the capability approach to study inequality, and not just poverty, poses even greater challenges, drawing on joint work with Tania Burchardt recently published in the Journal of Human Development and Capabilities. The final section will consider what adopting a capability perspective might imply in terms of understanding welfare state change. I will suggest that, despite the unorthodox nomenclature, the capability approach provides the basis for considering the impact of reforms on the quality of life, thus considering the impact of policies on both economic and non-economic dimensions of well-being.